Markers of nucleic acids and proteins oxidation among office workers exposed to air pollutants including (nano)TiO2 particles - Pelclova, Daniela; Zdimal, Vladimir; Kacer, Petr; Vlckova, Stepanka; Fenclová, Zdeňka; Navratil, Tomas; Komarc, Martin; Schwarz, Jaroslav; Zikova, Nadezda; Makes, Otakar; Zakharov, Sergey (Neuro-endocrinology letters, 2016)
OBJECTIVES: Experimental studies using nanoscale TiO2 have documented lung injury, inflammation, oxidative stress, and genotoxicity. Human health data are extremely scarce. METHODS: In exhaled breath condensate (EBC) and urine of 22 office employees occupationally exposed to TiO2 during their visit in the production workshops for average 14±9 min/day a panel of biomarkers of nucleic acids and proteins oxidation was studied, specifically 8-hydroxy-2-deoxyguanosine (8-OHdG), 8-hydroxyguanosine (8-OHG), 5-hydroxymethyl uracil (5-OHMeU), o-tyrosine (o-Tyr), 3-chlorotyrosine (3-ClTyr), and 3-nitrotyrosine (3-NOTyr). Examination was performed also in 14 comparable controls. RESULTS: The median respirable TiO2 mass concentration in the workshops was 0.40 mg/m3, median number concentration was 2.32×104 particles/cm3 with 80% of the particles being <100 nm in diameter. All 6 markers of oxidation were elevated in EBC in factory office employees relative to controls (p<0.01). Significant association was found between their job in TiO2 production plant and 5 markers of oxidation (except 3-NOTyr) in the EBC in multivariate analysis. No elevation of markers was detected in the urine. CONCLUSION: This pilot study suggests that even short nanoTiO2 exposure may lead to pulmonary oxidative stress; however this effect may be short-term and reversible. The clinical significance of these findings is unclear and more studies are needed.
Keywords: lidé středního věku; lidé; pracovní expozice; nemoci z povolání; Occupational Diseases; mužské pohlaví; Metal Nanoparticles; Adult; pilotní projekty; Titanium; Middle Aged; kovové nanočástice; Pilot Projects; Air Pollutants; titan; Humans; oxidační stres; Occupational Exposure; dospělí; Male; Oxidative Stress; látky znečišťující vzduch